Influence of Drying Methods on Physicochemical, Functional and Sensory Properties of Flour Made from Coconut Dregs - Nur Afiqah Shariman; Fazleen Izzany Abu Bakar (Enhanced Knowledge in Sciences and Technology, 2024)
This study explored the effects of diverse drying methods on coconut dregs flour and its consequent impact on chocolate coconut cakes. Noteworthy variations were observed in color, with oven-dried flour appearing notably darker (L* 27.82±0.10). Water activity revealed a 15% decrease in the food dehydrator sample (0.54±0.01), indicating enhanced storage stability. Texture assessments underscored the negative impact of oven drying, with a significant decrease in texture (2.37±0.38). Minimal pH variations were noted, while moisture content varied significantly, with higher levels in oven-dried samples (7.60±0.17). Functional properties exhibited method-dependent differences, such as bulk density (oven-dried: 0.52±0.13). Sensory evaluations unveiled distinct characteristics in aroma, taste, aftertaste, and overall acceptability, particularly in oven-dried samples. These findings highlight the pivotal role of drying methods in shaping the quality of coconut dregs flour and its food products, offering valuable insights for targeted product development aligned with consumer preferences. Further research avenues could explore specific compounds contributing to sensory disparities, facilitating refined product optimization.